Theology of Art in The Text of Adiparwa - Saitya, Ida Bagus Subrahmaniam (Mudra Jurnal Seni Budaya, 2024)
Adiparwa is the initial part of the Mahabharata, which can be viewed as consisting of two distinct parts. The first part presents the framework of the Bharata epic, and the second part contains the genealogy of the Pandavas and Kauravas. Adiparwa not only narrates the origins of the Kuru Dynasty and the various early events leading to the great war in Kuruksetra but also contains many profound theological and aesthetic elements. This study uses the theory of literary reception, which is based on the notion that literary works have always received responses from their readers since their publication. A qualitative research method with a theological approach is used in this study. The theology in the text of Adiparwa includes the concepts Nirguna Brahman and Saguna Brahman, in line with His attributes for creating the universe, embodied in Sanghyang Siwa with Bhatari Parwati. The aesthetics in the text of Adiparwa are described in the terms satyam, siwam, and sundaram. Satyam in the text of Adiparwa can be seen in the story of four quails that survived the burning of the Khandawa forest. The essence of siwam in the text of Adiparwa is described in the concept of God as Nirguna Brahman and Saguna Brahman. The values of sundaram are reflected in the beauty of Tilottama. The influence of theology on aesthetics is evident in the rituals described in the text of Adiparwa through the mabebasan tradition, usually performed during the atma wedana ceremony, via the Astikacarita story using the palawakya reading technique.